We should be just a number and we should embrace it. Issue 2 (3rd April 2017) - Kendall, Graham; Yee, Angelina; Hardy, Steven
Abstract : Purpose: The purpose of this paper is to support the use of unique identifiers for the authors of scientific publications. This, the authors believe, aligns with the views of many others, as it would solve the problem of author disambiguation. If every researcher had a unique identifier, there would be significant opportunities to provide even more services. These extensions are proposed in this paper. Design/methodology/approach: The authors discuss the bibliographic services that are currently available. This leads to a discussion of how these services could be developed and extended. Findings: The authors suggest a number of ways that a unique identifier for scientific authors could support many other areas of importance to the scientific community. This will provide a much more robust system that provides a much richer and more easily maintained, scientific environment. Originality/value: The scientific community lags behind most other communities with regard to the way it identifies individuals. Even if the current vision for a unique identifier for authors was to become more widespread, there would still be many areas where the community could improve its operations. This viewpoint paper suggests some of these, along with a financial model that could underpin the functionality.